Al-Farabi dan Ibnu Sina (Pemikiran Tentang Emanasi) - La Ode Samsudin; Indo Santalia (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Ibn Sina and al-Farabi argue that the process of the formation of this universe radiates everything from God through ten minds (al-‘Aql al-‘Asharah). God thinks about Himself; thought is a power, and the thought of God, the Almighty, is great and awesome, creating the first mind. The first mind also thinks about God and itself, so this power produces the second mind and the first sky. The second mind also thinks about God and itself and produces the third mind and the stars. And so on, the minds think about God and themselves and then produce the next minds and the planets. The third mind produces the fourth mind and Saturn. The fourth mind produces the fifth mind and Jupiter. The fifth mind produces the sixth mind and Mars. The sixth mind produces the seventh mind and the Sun. The seventh mind produces the eighth mind and Venus. The eighth mind produces the ninth mind and Mercury. According to Al-Farabi and Ibn Sina, both adapted the theory of emanation to explain the relationship between God and the creation of the universe. Al-Farabi saw nature as the result of emanation from God, who is the first being, while Ibn Sina emphasized that nature was created from a state of nothingness and not as part of God's substance. Although both agreed that nature is new and created, they faced criticism from Al-Ghazali who considered the theory of emanation could reduce God's position as Creator and potentially lead to pantheism. This criticism shows the tension between philosophical thought and theological teachings in the Islamic tradition.